"Comparative Literature" in the american academic bounds or comparative literature transformed in outrage - Naupert, Cristina (Tropelías: Review of Literary Theory and Comparative Literature, 1997)
Comparative Literature is still a very recent academic discipline in Spanish Universities and that is why we should study critically the development of this field of literary studies outside our own bounds. In this article we attempt to offer a panoramical review of the debate on new tendencies within the field of comparative literature which is actually going on among the american comparatists. We discuss in detail the Bernheimer Report 1993 because this document and its publication by the American Comparative Literature Association has been, in a certain manner, the detonator for this enthusiastic discussion of the discipline’s theoretical and methodological principies and its future development which would gain new impulses from an approximation to the areas of cultural and postcolonial studies.